OsNAC2 encoding a NAC transcription factor that affects plant height through mediating the gibberellic acid pathway in rice. (April 2015) - Chen, Xu; Lu, Songchong; Wang, Yaofeng; Zhang, Xuan; Lv, Bo; Luo, Liqiong; Xi, Dandan; Shen, Jiabin; Ma, Hong; Ming, Feng
Summary Plant height and flowering time are key agronomic traits affecting yield in rice (Oryza sativa). In this study, we investigated the functions in rice growth and development of OsNAC2, encoding a NAC transcription factor in rice. Transgenic plants that constitutively expressed OsNAC2 had shorter internodes, shorter spikelets, and were more insensitive to gibberellic acid (GA3). In addition, the levels of GAs decreased in OsNAC2 overexpression plants, compared with the wild‐type. Moreover, flowering was delayed for approximately 5 days in transgenic lines. The transcription of Hd3a, a flowering‐time related gene, was suppressed in transgenic lines. In addition, transgenic Arabidopsis plants expressing OsNAC2 were also more insensitive to GA3. The expression levels of GA biosynthetic genes OsKO2 and OsKAO were repressed. The expression of OsSLRL, encoding a repressor in the GA signal pathway, and OsEATB, which encodes a repressor of GA biosynthesis, were both enhanced. Western blotting indicated that DELLA also accumulated at the protein level. Dual‐luciferase reporter analyses, yeast one‐hybrid assays and ChIP‐qPCR suggested that OsNAC2 directly interacted with the promoter of OsEATB and OsKO2. Taken together, we proposed that OsNAC2 is a negative regulator of the plant height and flowering time, which acts by directly regulating key genes of the GA pathway in rice.